2014
DOI: 10.1016/j.ijid.2014.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Community-acquired culture-negative endocarditis: clinical characteristics and risk factors for mortality

Abstract: Culture-negative endocarditis patients presented with lower levels of C-reactive protein at admission and required more time for initiation of antibiotic therapy, although there was no difference in in-hospital mortality or long-term survival between culture-negative and culture-positive endocarditis patients. Diabetes mellitus and severe sepsis were associated with in-hospital death in patients with culture-negative endocarditis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
31
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 30 publications
0
31
0
Order By: Relevance
“…3,9 A study by Siciliano et al specifically reported mortality predictor in IE negative-culture patients, albeit with relatively fewer samples (51 cases in 9 years [1991][1992][1993][1994][1995][1996][1997][1998][1999]) compared with 146 cases in 5 years of this study. 2 This study differs from the other study in several aspects, namely risk factor definition population characteristics, sample size, and the novel inclusion of tricuspid annular plane systolic excursion as a mortality predictor. This new risk factor definition includes evaluation of acute kidney injury within the course of treatment, using criteria defined by the acute kidney injury network.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…3,9 A study by Siciliano et al specifically reported mortality predictor in IE negative-culture patients, albeit with relatively fewer samples (51 cases in 9 years [1991][1992][1993][1994][1995][1996][1997][1998][1999]) compared with 146 cases in 5 years of this study. 2 This study differs from the other study in several aspects, namely risk factor definition population characteristics, sample size, and the novel inclusion of tricuspid annular plane systolic excursion as a mortality predictor. This new risk factor definition includes evaluation of acute kidney injury within the course of treatment, using criteria defined by the acute kidney injury network.…”
Section: Discussionmentioning
confidence: 88%
“…Even with numerous studies on factors related to mortality in this condition, caveats exist due to different patients characteristics between the centers of study. 2,3,9 Furthermore, factors that are reported to be related to worse outcomes in one study often are not statistically significant across other studies. This study evaluates factors that are related to in-hospital mortality BCNIE patients at Harapan Kita National Cardiovascular Center, a tertiary hospital for heart and vascular disorders.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations